A biomimetic cerium-based biosensor for the direct visual detection of phosphate under physiological conditions. Issue 99 (11th November 2019) - Rossel, Thibaud; Creus, Marc
Abstract : An indicator displacement assay (IDA) was used to probe phosphate ions in an aqueous medium at neutral pH using a dinuclear cerium based complex [Ce2 (HXTA)] 3+ . Abstract : An indicator displacement assay (IDA) was used to probe phosphate ions in an aqueous medium at neutral pH using a dinuclear cerium based complex [Ce2 (HXTA)] 3+ . The homoleptic complex can be used to detect phosphate ions with nanomolar affinity either spectrophotometrically or with the naked-eye. To our knowledge, this is the first dinuclear cerium biomimetic IDA detection system with the highest affinity known to date for selective, naked-eye based phosphate recognition under physiological conditions (pH = 5–7) and even in pure water and complex samples such as sea water.